Dampak Keberagaman Agama terhadap Pola Interaksi Sosial Masyarakat Kota Makassar - M. Ridwan Said Ahmad; Yuyun Andinar; Muh Falak Cahyadi; A Jalal Al Afgan; Muh Syukur (CV. Syntax Corporation Indonesia, 2023)
Religion is one of the universal elements in human life, in which almost every human being lives. Religious life in urban communities has an impact on people’s behavior patterns. This is influenced by the human mindset that religion is a reference in interacting with society. So that in a society that has a diversity of religions (Islam, Christianity, Buddhism, Catholicism and Confucianism) it will have a major influence on the patterns of social interaction that exist in society, especially in urban communities. The city of Makassar has a diversity of people, especially in terms of religion, namely Islam, Christianity, Buddhism and others. This diversity arises due to urbanization carried out by the community with the aim of making a living, studying and so on. In research using qualitative research methods with a descriptive approach. Collecting data in this study using a purposive sampling technique. Data analysis techniques in this study used the Member Check technique. The results of the study show that in Makassar city society the impact of religious diversity on interaction patterns between people in Makassar city can be seen from their activities, for example cooperation, conflict, accommodation and competition activities. The impact of religious diversity in the city of Makassar can be divided into two, namely positive and negative impacts. The positive impact on the pattern of social interaction in society is to develop an attitude of tolerance and openness to anyone, while the negative impact is to trigger conflict between religions, as well as discrimination and exclusivism.